Thin-layer chromatography method for the simultaneous quantification and stability testing of alprazolam and mebeverine in their combined pharmaceutical dosage form. Issue 1 (1st January 2017) - Chhalotiya, Usmangani K.; Patel, Nishma M.; Shah, Dimal A.; Mehta, Falgun A.; Bhatt, Kashyap K.
Abstract: A sensitive, selective and precise high-performance thin-layer chromatographic method was developed and validated for the simultaneous determination of alprazolam and mebeverine, both as bulk drugs and in formulations. The method employed HPTLC aluminium plates that had been pre-coated with silica gel 60F-254 as the stationary phase, while the solvent system was acetone:methanol:acetic acid (6:4:0.1, v/v/v). The R f values of alprazolam and mebeverine were observed to be 0.80 ± 0.08 and 0.60 ± 0.05, respectively. The densitometric analysis was carried out in absorbance mode at 225 nm. The linear regression analysis for the calibration plots showed a good linear relationship for alprazolam and mebeverine over concentration ranges of 600 to 3600 ng/spot and 1000 to 6000 ng/spot, respectively. The limit of detection and the limit of quantification for alprazolam (mebeverine) were determined to be 63.97 (11.35) ng/spot and 193.85 (34.40) ng/spot, respectively. Alprazolam and mebeverine stock solutions were subjected to acid and alkali hydrolysis, chemical oxidation, dry heat degradation and photo-degradation. Both drugs were found to be susceptible to acid and alkali hydrolysis, chemical oxidation and photo-degradation, whereas both were found to be stable towards dry heat. The degraded product peaks were well resolved from the pure drug peak and displayed a significant difference in their R f values. Stressed samples were assayed using the developed HPTLC method. The proposed method was validated with respect to linearity, accuracy, precision and robustness. The method was successfully applied to the estimation of alprazolam and mebeverine in marketed formulations. Statistical analysis showed that the method is repeatable, selective, and precise.